(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
The main resources for biomass agro-ecotechnologies are cereal straw residues, energy crops and emergent vegetation from wetlands. The herbaceous biomass is a material of low density (20 – 60kg/m3) therefore new mobile equipment and technologies for biomass comminution and densification have to be worked out. To guarantee the quality of biomass briquettes in the handling and usage process, sufficient durability of briquettes should be provided. National Standards of biomass briquettes should be worked out in accordance with the requirements of International Standards. Dependence of Ultimate shear stress on wheat stalk material particle size in biomass briquettes was investigated. It was stated that ultimate shear stress increases for particle size in briquettes less than 0.5mm. Peat additive improves the density and ultimate shear strength of briquettes, but peat in combustion process increases the ash content. Therefore it is not necessary to add peat more than 50% in briquetting composition. Durability of reed stalk briquettes 1.7 times exceeds durability of wheat stalk briquettes. Maximal values of ultimate shear stress (1,5 MPa) and density (1,2 g/cm3) for pure peat (100%) briquettes was obtained.